Determination of Fatty Acid Composition, Cholesterols, Triglyceride and Vitamin Contents of Some Selected Fishes from Assam, India - Sarkar, Arjina P.; Basumatary, Sanjay; Sarma, Santanu; Das, Sandeep (Current Nutrition & Food Science, 2020)
Background: Fishes are good sources of the fatty acids such as ω-3 and ω-6 polyunsaturated fatty acids, and fat-soluble vitamins for human consumption which play vital roles for various biological processes in the body and help in the proper growth and prevention of diseases. Objective: The objective of the present study was to determine the fatty acid composition, cholesterols, triglyceride and vitamin contents of some selected fishes from Hel river, Assam, India. Methods: Fatty acid composition of fish species was examined using gas chromatography-mass spectrometry, lipid components were determined following the reported methods and vitamins A and D contents were investigated by reversed-phase high-performance liquid chromatography. Results: Fatty acid compositions varied from 51.20-89.47% of saturated fatty acids, 0.27-19.68% of monounsaturated fatty acids and 1.75-30.76% of polyunsaturated fatty acids. Eicosapentaenoic acid and docosahexaenoic acid ranged from 0.54-22.30% and 1.26-18.85%, respectively. The fish species showed varying amounts of lipid components. The vitamins A and D were found in the range of 15.85-1287.0 μg/100 g and 45.0-677.24 μg/100 g, respectively. Conclusion: The fish species of this study are found rich in ω-3 polyunsaturated fatty acids such as eicosapentaenoic acid and docosahexaenoic acid along with noticeable amounts of vitamins A and D. Hence, these fish species have the potentials to serve as the natural dietary supplements for ω-3 fatty acids and other nutrients.
Keywords: fatty acid composition